The Influence Of Motivation On Employee Performance In The Regional Disaster Management Agency Of The City Of Sukabumi - Ghania Khalda; Ike Rachmawati; Tuah Nur (Program Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to determine the effect between motivation and employee performance at the Sukabumi City Regional Disaster Management Agency. This research method uses a quantitative associative approach. This study's population were all Sukabumi City Regional Disaster Management Agency employees. The sampling technique in this study used nonprobability sampling with a saturated sample, namely employees at the Sukabumi City Regional Disaster Management Agency, totalling 49 employees. Data was collected using observation, documentation, questionnaire distribution and interview methods. Data analysis in this study was carried out by correlation coefficient test, coefficient of determination test, simple linear regression analysis test, and data processing using IBM SPSS Statistics 26. Based on the study's results, it is known that the correlation coefficient test obtained a positive correlation value which indicates a closeness with a high category. The coefficient of determination (R2) data results showed a positive influence between motivation and employee performance at the Sukabumi City Regional Disaster Management Agency of 0.594. This means that the magnitude of the influence of motivation on performance is 59.4%, while 40.6% is influenced by other factors not examined in this study.